Effect of Prayer Practice on Physical Fitness and Mental Health of Adult Muslims: A Systematic Study - Wahyuni, Wahyuni; Ahmad Ari Suryono MZ (Universitas Muhammadiyah Surakarta, 2025)
Introduction: Prayer is a very important act of worship and a daily obligation for Muslims. In the last few decades, there have been many studies that discuss the benefits of prayer on human health both physically and mentally. Prayer can be categorised as a type of physical exercise as it involves planned and repetitive body movements. This study aims to determine the effect of prayer on physical fitness and mental health in adults. Methods: This study used a systematic review method, by reviewing Quartile Q1-Q3 articles that used quantitative research and were published in the last 10 years. Articles were searched in 4 databases (Google Scholar, Science Direct, Pubmed, Springer Open). Selected articles were then assessed for quality and synthesised narratively. Results: There were 7 articles that met the inclusion criteria, all articles showed a positive effect of prayer implementation on physiological conditions related to physical fitness and mental health. Conclusion: Prayer has a positive effect on physical fitness by improving haemodynamic, immune, metabolic and muscular flexibility and potentially preventing oxidative stress. In mental health, prayer has an effect on peace of mind that can balance hormones and reduce gene expression triggered by stressful conditions.